Design of high electromagnetic compatibility wireless power transfer system for wireless motors - Zhang, Xiongce (Nanyang Technological University, 2024)
Featuring on characteristics over wired charging, such as convenience and minimizing losses, wireless power transfer (WPT) for wireless motors is a critical technology for autonomous driving. As WPT technology for electric vehicle motors progresses towards higher frequencies, issues such as increased high-frequency losses in coupling coils need to be addressed. This thesis researches and constructs the coupling coils structure of high-frequency wireless charging systems for wireless motors. The main research content includes: 1. Based on regarding the present state of research, the compensation circuit topologies and magnetic coupling structures are theoretically analyzed. Mathematical calculations are performed on four basic compensation circuit topology models, ultimately selecting the SS-type compensation circuit topology for further parameter study. Coupled Mode Theory and mutual inductance model theory, as well as Proximity and Skin Effect, are analyzed to lay the foundation for the study of wireless charging systems. 2. Coupling coils are designed using SolidWorks, and the magnetic coupling system is modeled in ANSYS HFSS to test the impact of changing the position of the coil on the coupling coefficient. Subsequently, amounts of turns, pitch, and material of the coils are varied to test their impact on the coupling coefficient. Suitable coil parameters are selected to enhance system transmission efficiency.